MOLECULAR DETECTION OF PSEUDOMONAS AERUGINOSA ISOLATED FROM MINCED MEAT AND STUDIES THE PYOCYANIN EFFECTIVENESS ON PATHOGENIC BACTERIA - D. A. Qasim (The Iraqi Journal of Agricultural science, 2019)
This study was aimed to collected Minced meat from the local markets in Baghdad governorate during 2018, and examined for the presence of Pseudomonas aeruginosa, in order to extract and purify pyocyanin and examined it as an antimicrobial activity against pathogenic bacteria in foods. Fifteen isolates were isolated from 50 samples and identified as P. aeruginosa using the API20E system and finally confirmed with PCR using 16SrRNA gene. Four tested media were used for the production of pigment after incubation within 72 h, One strain which given a vigorous pigmentation was chosen and extracted with chloroform and HCl then analyzed with Gas chromatography (GC-Mass) which showed a sharp peak at the time of acquisition of 27.13 minutes at the chromatographic analysis recognized with mass spectrometry as Hemipyocanin (alpha-hydroxy phenazine) which produced molecular ion with intensive peak at 205 m/z. Agar well diffusion technique was applied for estimating the antimicrobial activity of purified (pyocyanin) with variable concentrations (25, 50, 75 and 100 mg/ml) which monitored toward  Gram-negative and  Gram-positive bacteria that isolated of minced meat. Escherichia coli and staphylococcus aureus was the most affected with pyocyanin were followed by Serratia marcescens and Klebsiella sp. at the same level. While Enterobacter sp, Bacillus cereus, Proteus mirabilis, and Proteus vulgaris showed intermediate sensitivity, the Pseudomonas fluorescens was shown low sensitivity to pyocyanin.